2019
DOI: 10.1016/j.celrep.2019.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulation of Metabolism Is Required for CD8+ T Cell Anti-tumor Immunity

Abstract: Highlights d Inactivation of T cell autophagy results in enhanced tumor rejection d T cells deficient in autophagy show increased glucose uptake and lactate production d Reduction in SAM transcriptionally reprograms immune cells toward effector memory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 55 publications
4
125
0
Order By: Relevance
“…Certain subsets of suppressor immune cells may be more or less susceptible to autophagy inhibition. produced striking rejection of tumor implants in syngeneic mouse tumor models (100). Work by Mgrditchian and colleagues has shown that genetic inhibition of BECN1 augments infiltration of T cells into the immune microenvironment (101).…”
Section: Autophagy and Tumor Immunitymentioning
confidence: 99%
“…Certain subsets of suppressor immune cells may be more or less susceptible to autophagy inhibition. produced striking rejection of tumor implants in syngeneic mouse tumor models (100). Work by Mgrditchian and colleagues has shown that genetic inhibition of BECN1 augments infiltration of T cells into the immune microenvironment (101).…”
Section: Autophagy and Tumor Immunitymentioning
confidence: 99%
“…175,176 Autophagy also supports T cell function in anti-tumor immunity. 177 In addition, autophagy is upregulated in Treg cells compared to naïve CD4 + T cells, and it promotes Treg cell responses for suppression of autoimmunity, anti-tumor immunity and other inflammatory disorders. 26,178 These effects are attributed, in part, to reduced Treg cell survival in the absence of autophagy.…”
Section: Autophagymentioning
confidence: 99%
“…26 Heightened glycolysis has also been observed in autophagy-deficient CD8 + T cells. 177 Thus, autophagy supports many aspects of T cell fitness and function.…”
Section: Autophagymentioning
confidence: 99%
“…Importantly, CD8 + T cell memory generation and maintenance require of autophagy activity [138]. Recent works indicate that the ability of autophagy to reprogram CD8 + T cell metabolism, contributes in modulation of the efficacy of anti-tumor CD8 + T cell responses [139,140] (Figure 2).…”
Section: Macroautophagy In the Adaptive Immune Responsementioning
confidence: 99%